2008
DOI: 10.1111/j.1365-2648.2008.04841.x
|View full text |Cite
|
Sign up to set email alerts
|

Older people’s expectations regarding ageing, health‐promoting behaviour and health status

Abstract: It may be necessary for nurses to make an effort to improve older people's expectations about ageing to help them achieve good health. Nursing interventions to improve these expectations need to be used in conjunction with an emphasis on older people's active involvement in health-promoting behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
79
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 17 publications
9
79
2
1
Order By: Relevance
“…It is also difficult to draw meaningful comparisons between these findings and research that focuses on the relationship between mental health and aging, as this work predominantly has been conducted with clinical populations (Golub et al, 2006;Blotman et al, 2007) or is concerned with the expectations of an older persons population in the community regarding their future health status (Sarkisian et al, 2002;Kim, 2009). Similar results to the current study were found by Ziersch and Baum (2004).…”
Section: Discussionsupporting
confidence: 88%
“…It is also difficult to draw meaningful comparisons between these findings and research that focuses on the relationship between mental health and aging, as this work predominantly has been conducted with clinical populations (Golub et al, 2006;Blotman et al, 2007) or is concerned with the expectations of an older persons population in the community regarding their future health status (Sarkisian et al, 2002;Kim, 2009). Similar results to the current study were found by Ziersch and Baum (2004).…”
Section: Discussionsupporting
confidence: 88%
“…ERA measures expectation of age-related decline in three domains: physical health, mental health, and cognitive function. ERA is under researched in relation to DM; however, studies conducted among general older adults (Kim, 2009) and middle-aged adults (Joshi et al, 2010) have shown positive correlation with perceived health. Low ERA was significantly associated with low DMSE, which is consistent with previously reported findings (Joshi et al, 2010;Kim, 2009).…”
Section: Factors Influencing Diabetes Self-carementioning
confidence: 96%
“…ERA is under researched in relation to DM; however, studies conducted among general older adults (Kim, 2009) and middle-aged adults (Joshi et al, 2010) have shown positive correlation with perceived health. Low ERA was significantly associated with low DMSE, which is consistent with previously reported findings (Joshi et al, 2010;Kim, 2009). Assessment of ERA will help identify patients for whom interventions to promote self-efficacy can be directed.…”
Section: Factors Influencing Diabetes Self-carementioning
confidence: 96%
“…Levy et al (2002) demonstrated that positive ERA are associated with better physical function while aging, as well as increased longevity. Positive ERA were also related to better self-reported physical and mental health, and this relationship between ERA and health was partially mediated by engagement in health-promoting behaviors such as physical activity, stress management, and interpersonal relations (Kim, 2009). Self-perception of aging can also influence individuals’ engagement in other health-promoting behaviors such as having regular physical examinations, eating a healthy balanced diet, limiting use of alcohol and/or tobacco, and participating in exercise, as well as their use of health care resources (Levy & Myers, 2004).…”
Section: Health and Expectations Regarding Agingmentioning
confidence: 99%